The Bucobello 322 ka-fossil-bearing volcaniclastic-flow deposit in the eastern Vulsini Volcanic District (central Italy): Mechanism of emplacement and insights on human activity during MIS 9. (20th July 2020) - Di Buduo, G.M.; Costantini, L.; Fiore, I.; Marra, F.; Palladino, D.M.; Petronio, C.; Rolfo, M.F.; Salari, L.; Ceruleo, P.; Florindo, F.; Gaeta, M.; Gatta, M.; et al.
Abstract: We present a multidisciplinary study of a fossiliferous site located in the Vulsini Volcanic District, on the western side of the Tiber River Valley north of Rome, highlighting the peculiar geologic factors that contributed to the origin and preservation of an outstanding archaeological record testifying of the early human frequentation in this region. Mighty explosive eruptions since at least 500 ka affected the investigated area eventually culminating in the formation of the huge Bolsena caldera. Tectonic deformation accompanying volcanic activity caused large fault displacements, shaping the ground surface and contributing to route the path, and possibly to trigger, the catastrophic emplacement of volcaniclastic flows. A sedimentary trap originated by fault scarp cutting through a streambed was likely the cause for the large accumulation of bones and stone artifacts ripped up and carried by a volcaniclastic flow at 322 ka. The analysis of the fossil assemblage reveals both gnawing traces by carnivores and cut-marks from the percussion tools employed by humans to butch the carcasses. However, the occurrence of retouched and unretouched blanks within the lithic assemblage also testifies for provenance from a wider area of human activity, which included hunting and scavenging, probably at a nearby butchering site.